Objetos de ensino: a renovação pedagógica e material da escola primária no Brasil, no século XX - Souza, Rosa Fátima de [UNESP] (Universidade Federal de Uberlândia (UFU), Setor de Educação, 2013)
This article aims at analyzing the role of the objects of learning in the propositions for innovation of primary schools during the 20th century, highlighting the changes in the composition of school subjects having in mind the objects that were introduced and marked out as relevant for school modernization and those that remained or were redefined in terms of their finality and uses. The examination of three significant moments of the implementation of innovations in the elementary school is intended: the modernization by the intuitive method at the turn of the century; the propositions of Escola Nova between the 1930s and the 1950s; and the renovation represented by educational technology in the 1960s and 1970s.

O objetivo deste texto é analisar o papel dos objetos de ensino nas proposições de renovação da escola primária durante o século XX assinalando as mudanças na composição material das escolas tendo em vista os objetos que foram introduzidos e ressaltados como relevantes para a modernização da educação e aqueles que permaneceram ou foram redefinidos em termos de finalidades e usos. Pretende-se, dessa forma, examinar três momentos significativos de implantação de inovações na escola elementar: a modernização pelo método intuitivo na virada do século XIX para o século XX, as proposições da Escola Nova nas décadas de 1930 a 1950 e a renovação representada pela Tecnologia Educacional nas décadas de 1960 e 1970.
Objects of learning: the pedagogic and material renovation of elementary school in Brazil, in the 20th century
Keywords: cultura material escolar; objetos escolares; renovação do ensino primário; história da educação; ensino primário; school material culture; school objects; renovation of primary school education; history of education; primary school education